Tribological Performance of Silahydrocarbons Used as Steel-Steel Lubricants under Vacuum and Atmospheric Pressure. (16th April 2014) - Wang, Hai-Zhong; Zhang, Song-Wei; Qiao, Dan; Feng, Da-Peng; Liu, Wei-Min
Abstract : The silahydrocarbons of tetraalkylsilanes with different substituted alkyl groups (named as SiCH) were synthesized and evaluated as lubricants for steel-steel contacts by a home-made vacuum four-ball tribometer (VFBT-4000) under atmospheric pressure and under vacuum pressure (5 × 10 - 4  Pa). The SiCH oils possess better thermal stability, low temperature fluidity, and lower saturated vapor pressure than those of multialkylatedcyclopentanes (MACs). The tribological performances of the SiCH oils are also superior to those of MACs and PFPE-Z25 in terms of friction-reduction ability and antiwear capacity under sliding friction at vacuum. The SEM/EDS and XPS results reveal that the boundary lubricating film consisting of ( -O-Si-R- ) n compounds is formed by tribochemical reactions and serious adhesion wear under atmospheric pressure and the film consisting of ( -Si-R-Si- ) n compounds is formed on the worn surface under vacuum pressure.